Investigation of physical activity levels and eating attitudes of individuals doing sports: Physical activity levels and eating attitudes in sports - Keyf, Erdil; Ağgön, Eser (Progress in Nutrition, 2020)
Aim: The aim of this study is to investigate the relationship between physical activity levels and eating attitudes of individuals who do sports in order to improve their life quality according different variables. Materials and Methods: A total of 385 athletes, 63 women and 322 men, aged between 18-45 who do sports in various gyms in Adana city center to improve their life quality took part in the survey voluntarily. The athletes completed the International Physical Activity Questionnaire – Short Form (IPAQ-SF) and Eating Attitudes Test (EAT-40). Results: According to the results of our research, it is specified that 16.4% of individuals who do sports are females and 83.8% of them are males, 75.3% have a normal eating attitude and 24.7% have a disordered one, 65.7% pay attention to their nutrition whereas 34.3% do not, and 43.1% take supplements. There is no statistically significant difference between pyhsical activity levels and the eating attitudes of the participants according to the gender and education levels (p>0,5). On the other hand, it is observed that there is a statistically significant difference between physical activity levels and eating attitude scores according to paying attention to their nutrition, to quantity of having snacks and to taking supplements (p<0,5). Moreover, it is discovered that there is no statistically significant relation between physical activity and general eating attitude scores of the participants. Conclusion: In this research, it is observed that individuals who pay attention to their nutrition have a higher physical activity level but that individuals who do sports tend more to have a skipping a meal attitude. It can be stated that the benefits of exercise to human health will be more available with correct eating habits. Keywords: Physical Activity, Nutrition, Eating Attitude